Frailty assessment as independent prognostic factor for patients ≥65 years undergoing urgent cholecystectomy for acute cholecystitis. Issue 4 (April 2023) - Rosa, Fausto; Covino, Marcello; Russo, Andrea; Salini, Sara; Forino, Raffaele; Della Polla, Davide; Fransvea, Pietro; Quero, Giuseppe; Fiorillo, Claudio; La Greca, Antonio; Sganga, Gabriele; Gasbarrini, Antonio; et al.
Abstract: Background: To evaluate, in a prospective observational cohort study of adults ≥65 years old, the frailty status at the emergency department (ED) admission for the in-hospital death risk stratification of patients needing urgent cholecystectomy. Methods: Clinical variables and frailty status assessed in the ED were evaluated for the association with major complications and the need for open surgery. The parameters evaluated were frailty, comorbidities, physiological parameters, surgical approach, and laboratory values at admission. Logistic regression analysis was used to identify independent risk factors for poor outcomes. Results: The study enrolled 358 patients aged ≥65 years [median age 74 years]; 190 males (53.1%)]. Overall, 259 patients (72.4%) were classified as non-frail, and 99 (27.6%) as frail. The covariate-adjusted analysis revealed that frailty ( P< 0.001), and open surgery ( P = 0.015) were independent predictors of major complications. Frailty, peritonitis, constipation at ED admission, and Charlson Comorbidity Index ≥ 4 were associated with higher odds of open surgical approach (2.06 [1.23 - 3.45], 2.49 [1.13 – 5.48], 11.59 [2.26 – 59.55], 2.45 [1.49 – 4.02]; respectively). Discussion: In patients aged ≥65 years undergoing urgent cholecystectomy, the evaluation of functional status in the ED could predict the risk of open surgical approach and major complications. Frail patients have an increased risk both for major complications and need for "open" surgical approach.